The potential value of thromboelastography and conventional coagulation detection in guiding the management of venous thrombosis after traumatic brain injury - Jingchao Zhou; Zhenghao Wang; Rui Pan; Pengcheng Zhang; Hechun Xia; Wei Wang; Zhanfeng Niu (PLoS ONE, 2026)
Background Coagulation disorders are serious complications of traumatic brain injury (TBI), yet the predictive value of thromboelastography (TEG) for deep vein thrombosis (DVT) in this population remains unclear. This study aimed to assess the TEG profiles and four conventional coagulation parameters in patients with isolated TBI at multiple time points to predict the risk of early DVT. Methods In this retrospective study, 71 patients with isolated TBI were enrolled and categorized into thrombosis (n = 30) and non-thrombosis (n = 41) groups based on Doppler ultrasound and pulmonary angiography findings. Conventional coagulation parameters (PT, APTT, FIB, D-Dimer, TT, PLT) and TEG parameters (R, α-angle, MA) were systematically measured at 24, 72, and 168 hours post-injury. Statistical analyses included group comparisons and binary logistic regression to identify independent predictors of thrombosis. Results Patients who developed thrombosis had significantly lower Glasgow Coma Scale (GCS) scores (p < 0.001). Coagulation profiles evolved dynamically: D-dimer and TEG-MA were elevated at 24 hours; PT, fibrinogen, and D-dimer were higher at 72 hours; PT, D-dimer, and TEG α-angle remained elevated at 168 hours. Multivariate analysis identified lower 24-hour GCS score (OR=0.595, p < 0.001) and elevated PT at 72 and 168 hours as independent predictors of DVT. D-dimer was predictive at 72 hours (OR=1.244, p = 0.023). TEG parameters, despite showing hypercoagulability, did not independently predict thrombosis. Conclusions In isolated TBI, coagulation abnormalities evolved dynamically during the first week after injury. Conventional coagulation parameters, particularly prothrombin time and D-dimer, were more informative for venous thrombosis risk assessment, whereas TEG reflected global hypercoagulability without providing independent predictive value.